Patients’ and Nurses’ Perceptions of Respect and Human Presence Through Caring Behaviours: A Comparative Study - Efstathiou, Georgios; Tsangari, Haritini; Suhonen, Riitta; Leino-Kilpi, Helena; Patiraki, Elisabeth; Karlou, Chryssoula; Balogh, Zoltan; Palese, Alvisa; Tomietto, Marco; Jarosova, Darja; Merkouris, Anastasios; Papastavrou, Evridiki (My University, 2012)
Although respect and human presence are frequently reported in nursing literature, these are poorly defined within a nursing context. The aim of this study was to examine the differences, if any, in the perceived frequency of respect and human presence in the clinical care, between nurses and patients. A convenience sample of 1537 patients and 1148 nurses from six European countries (Cyprus, Czech Republic, Finland, Greece, Hungary and Italy) participated in this study during autumn 2009. The six-point Likert-type Caring Behaviours Inventory-24 questionnaire was used for gathering appropriate data. The findings showed statistically significant differences of nurses’ and patients’ perception of frequency on respect and human presence. These findings provide a better understanding of caring behaviours that convey respect and assurance of human presence to persons behind the patients and may contribute to close gaps in knowledge regarding patients’ expectations.
Keywords: Caring behaviours; International; Nursing; Presence; Respect